Maya Angelou : adventurous spirit : from I know why the caged bird sings (1970) to Rainbow in the cloud, The wisdom and spirit of Maya Angelou (2014) - Wagner-Martin, Linda (New York : Bloomsbury Academic, an imprint of Bloomsbury Publishing Inc, 2016)
'A comprehensive biographical and critical reading of the works of American poet and memoirist Maya Angelou (1928-2014). Linda Wagner-Martin covers all six of Angelou's autobiographies, as well as her essay and poetry collections, while also exploring Angelou's life as an African American in the United States, her career as stage and film performer, her thoughtful participation in the Civil Rights actions of the 1960s, and her travels abroad in Egypt, Africa, and Europe. In her discussion of Angelou's methods of writing her stunning autobiography, which began with the 1970 publication of I Know Why the Caged Bird Sings, Wagner-Martin writes about the influences of the Harlem Writers Group (led by James Baldwin, Paule Marshall, and John O. Killens) as well as Angelou's significant friendships with Malcolm X, Martin Luther King, Jr., and other leaders from both international and African American United States cultures. Crucial concepts throughout include the role of oral traditions, of song and dance, of the spiritualism of art based on religious belief, of Angelou's voiced rhythms and her polished use of dialogue to convey more abstract'meaning.' Wagner-Martin shows that, viewing herself as a global citizen, Angelou never lost her spirit of adventure and discovery as well as her ability to overcome'--
'A comprehensive critical and biographical reading of Maya Angelou's life and work, from I Know Why the Caged Bird Sings (1970) to His Day Is Done, A Nelson Mandela Tribute (2014)'--
Machine generated contents note: -- Preface -- Chapter One: Marguerite Annie Johnson, April 4, 1928 -- Chapter Two: Ambivalence Is Not So Easy -- Chapter Three: I Know Why the Caged Bird Sings -- Chapter Four: Gather Together in My Name -- Chapter Five: Music, poetry, and being alive -- Chapter Six: Singin' and Swingin' and Gettin' Merry Like Christmas -- Chapter Seven: The Heart of a Woman -- Chapter Eight: Africa -- Chapter Nine: A Song Flung Up to Heaven -- Chapter Ten: Poems and the Public Spotlight -- Chapter Eleven: From Autobiography to the Essay -- Chapter Twelve: Maya Angelou as Spirit Leader.
Includes bibliographical references (pages 211-236) and index.
Keywords: Angelou, Maya; Angelou, Maya -- Criticism and interpretation; Authors, American -- 20th century -- Biography; African American authors -- Biography; Civil rights workers -- Biography